Toll-like receptor 7 and 8 polymorphisms: Associations with functional effects and cellular and antibody responses to measles virus and vaccine - Clifford, H.; Yerkovich, S.; Khoo, S.; Zhang, Guicheng; Upham, J.; Le Souëf, P.; Richmond, P.; Hayden, C. (2012)
Successful defence against viral pathogens requires the rapid recognition of virus-specific "danger signals" and the activation of both innate and adaptive immunity. Toll-like receptors (TLR) 7 and 8 play a critical role in the elimination of viruses by recognising the common viral component, single stranded (ss)RNA. Measles virus, an ssRNA virus, continues to cause serious morbidity and mortality worldwide despite available measles vaccines. TLR7 and TLR8 genetic variation may cause functional alterations that result in impaired responses to measles. In a population of 12-month-old Australian infants, receptor protein expression was examined to assess the functionality of TLR7 and TLR8 polymorphisms, and the effects of these polymorphisms on cellular and antibody responses after the first measles vaccine dose were investigated. TLR7 Leu11Gln showed associations with TNF-a responses after ligand (imiquimod) stimulation in males only (P = 0.040), and non-responders were more likely to be Gln males (P = 0.044). TNF-a non-responders after imiquimod also had higher percentages of TLR8 -4284TT (69.6%) (P = 0.001) and TLR8 -558CC (69.6%) (P = 0.002) in females. Receptor protein expression after imiquimod or measles stimulation was not significantly altered compared with baseline, nor was it affected by genotype. None of the TLR7 or TLR8 polymorphisms studied were associated with measles-specific cytokine levels or with measles IgG levels. In conclusion, we report gender-specific associations with TLR7 and TLR8 polymorphisms and TNF-a cellular responses to its ligand. However, we found no evidence of any functional effects of TLR7 or TLR8 polymorphisms on receptor expression, measles-specific cellular responses or measles vaccine antibody responses. © 2011 Springer-Verlag.